Multiple family group service delivery model for children with disruptive behavior disorders: Impact on caregiver stress and depressive symptoms - Gopalan, Geetha; Bornheimer, Lindsay A.; Acri, Mary; Winters, Andrew; O’Brien, Kyle H.; Chacko, Anil (Journal of Emotional and Behavioral Disorders, 2018)
Disproportionately high rates of caregiver stress and depression are found among poverty-impacted communities, with high levels of caregiver stress and depression putting youth at heightened risk for the onset and perpetuation of disruptive behavior disorders. The purpose of this study was to examine the effects of a behavioral parent training program called the 4Rs and 2Ss for Strengthening Families Program (4R2S) on caregiver stress and depressive symptoms among 320 youth aged 7 to 11 and their families assigned to either the 4R2S or services as usual (SAU) condition. Among caregivers with clinically significant (CS) scores at baseline, 4R2S participants manifested significantly reduced scores on the stress and depressive symptom scores to SAU participants at 6-month follow-up. Findings suggest that 4R2S may reduce caregiver stress and depressive symptoms among those caregivers initially manifesting CS levels of stress or depressive symptoms.
Keywords: dept.rec; dept.swk; peer-reviewed